Temporal lags and carbon-water coupling in the dry-hot valleys of southwest China over the past two decades - Wang, Dawei; Jia, Duni; Zhang, Yao; Tao, Xin; Han, Feibing; Ma, Yanbin; Guo, Yu; Li, Jinshan; Li, Lili (Frontiers in Environmental Science, 2025)
Water use efficiency (WUE), as an important parameter of ecosystem carbon-water cycle, is an important index to assess vulnerability to extreme drought events. However, little was known about the corresponding cumulative and lagged responses of WUE to drought in the dry and hot valleys of Southwest China. This region is covered by alpine-valley landscapes, fragmented topographic features, Foehn Effect, where drought response mechanisms are not yet fully understood. This study analyzed the spatial-temporal variation of WUE from 2000 to 2020 in Binchuan (BC) and Yuanmou (YM) regions and the time-lag and -accumulation effects of 12 monthly self-calibrating Palmer Drought Index (scPDSI) on the WUE. Given the variability of vegetation types, land use/cover change data was used to investigate the variability of WUE between the two areas. Subsequently, the Pearson Correlation coefficient (Pearson, R) analysis, considering the influence of drought on time-lag and -accumulation effects, was used to analyze the response mechanism of water use efficiency to scPDSI in BC and YM comparatively. The results show that (1) From 2001 to 2020, BC’s average annual WUE was 2.59 gC m−2 mm−1, and YM’s was 2.84 gC·m−2·mm−1, with similar spatial distributions. (2) Over the past 2 decades, BC’s WUE increased steadily at a rate of 0.012 gC m-2 mm−1 a−1, while Yuanmou’s WUE grew at 0.0082 gC m-2 mm−1 a−1. (3) The lag response of WUE to drought is minimal in both regions, with BC’s cultivated land showing greater sensitivity to drought than YM. (4) The cumulative effect of drought on WUE across different land uses in both BC and YM is generally small, with the lowest sensitivity in forest land to drought.